2021
DOI: 10.1016/j.tifs.2021.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Potential protective mechanisms of green tea polyphenol EGCG against COVID-19

Abstract: Background The world is in the midst of the COVID-19 pandemic. In this comprehensive review, we discuss the potential protective effects of (−)-epigallocatechin-3-gallate (EGCG), a major constituent of green tea, against COVID-19. Scope and approach Information from literature of clinical symptoms and molecular pathology of COVID-19 as well as relevant publications in which EGCG shows potential protective activities against COVID-19 is integrated and evaluated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
98
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(98 citation statements)
references
References 203 publications
(257 reference statements)
0
98
0
Order By: Relevance
“…The broad spectrum of polyphenols such as tannins ( Mehany et al, 2021 ; Umeoguaju et al, 2021 ) and catechins e.g., from green tea ( Chourasia et al, 2021 ; Zhang et al, 2021 ) strongly interact with viral envelope proteins and were found to exhibit antiviral activity. To assess the antiviral potential of polyphenol-containing EPs 7630, we infected human lung cells with highly pathogenic human coronaviruses in the presence of EPs 7630.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The broad spectrum of polyphenols such as tannins ( Mehany et al, 2021 ; Umeoguaju et al, 2021 ) and catechins e.g., from green tea ( Chourasia et al, 2021 ; Zhang et al, 2021 ) strongly interact with viral envelope proteins and were found to exhibit antiviral activity. To assess the antiviral potential of polyphenol-containing EPs 7630, we infected human lung cells with highly pathogenic human coronaviruses in the presence of EPs 7630.…”
Section: Discussionmentioning
confidence: 99%
“…is efficacious as a treatment for acute bronchitis ( Matthys et al, 2003 ; Chuchalin et al, 2005 ; Matthys and Funk, 2008 ; Kamin et al, 2010a ; Kamin et al, 2010b ; Matthys et al, 2010 ; Kamin et al, 2012 ), sinusitis ( Bachert et al, 2009 ), common cold ( Lizogub et al, 2007 ; Riley et al, 2018 ; Riley et al, 2019 ), and acute non-GABHS tonsillopharyngitis ( Bereznoy et al, 2003 ). Similar to other proanthocyanidin-containing substances such as green tea ( Chourasia et al, 2021 ; Zhang et al, 2021 ), in vitro data suggest that EPs 7630 has broad-spectrum antiviral and antibacterial activity as well as immunomodulatory effects, although the precise mechanism of action has not been identified ( Moyo and Van Staden, 2014 ). Distinct antiviral effects of EPs 7630 have been observed in concentrations up to 100 μg/ml, with activity reported mainly against enveloped viruses such as influenza A virus (IAV; e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Although the major tea catechin EGCG showed weaker 3CLpro inhibition, it was reported to inhibit SARs-CoV-2 infections through different mechanisms ( Henss et al, 2021 ; Zhang et al, 2021 ). Severe SARs-CoV-2 infection and high mortality are mainly caused by cytokine storm and inflammation, triggering a huge burden of oxidative imbalance on the immune system ( El‐Missiry et al, 2020 ; Zhang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The catechin (−)-epigallocatechin-3-gallate (EGCG), the main flavonoid compound of green tea, has recently been documented in a comprehensive review article that demonstrated its potential protective effect against SARS-CoV-2 infection via multiple mechanisms of action that target viral or host cell proteins evaluated in various preclinical experiments. The protective effects of EGCG are related to preventing cytokine storm-associated acute lung injury/acute respiratory distress syndrome, thrombosis by inhibiting tissue factors and activating platelets, sepsis by inactivating redox-sensitive high mobility group box 1 (HMGB1), and lung fibrosis via increasing Nrf2 and hindering NF-κB activation [ 136 ].…”
Section: Phenolic Phytochemicals and Phenolic Rich Herbal Medicine Against Coronavirus-associated Lung Injurymentioning
confidence: 99%
“…15 COPD patients [188] Chronic inflammation (asthma) 9,709 individuals [189] Asthma in the elderly as risk factor; plant phenolics against asthma nd chronic inflammation Inflammation, allergies, immunity [13,190,191] Metabolic ill patients with obesity 28 individuals with metabolic syndrome [192] Inflammation in obese individuals Metabolic inflammation and oxidative stress (obesity), [43,193,194] Vascular function 19 essential untreated hypertensive patients [195] Cardiovascular functions, protection against cardiovascular damage Cardiovascular protection, inflammation, anti-thrombotic effects [136,151,152,196,197] Prostate cancer 73 prostate cancer patients [198][199][200] Modulation of cancer patients immune responses, protection against poor outcome Modulation of immunity, inflammation, prevention [19,113,201,202] In vitro (prostate cancer cell lines)…”
Section: Conclusion and Future Perspectives In The Framework Of 3pmmentioning
confidence: 99%